Bacterial crowd control: AIP-based analogues and solonamides modulate staphylococcal virulence - Hampson, Robert W. (2016)
This thesis details research in three areas, in attempts to produce more effective inhibitors of the staphylococcal agr quorum sensing system. The non-ribosomal peptide synthase biosynthetic cluster responsible for the production of the aureusimines represents roughly 0.5% of the S. aureus genome. However, their function is yet to be elucidated. Research detailed herein develops a new reliable method for synthesis for these natural products. Efforts to discover the biological target or function of these compounds using affinity chromatography is reported. Further biological investigations revealed that the aureusimines are mild antagonists of the agr system. Weak inhibition of CCL-2 mediated chemotaxis of monocytes and staphylococcal biofilm formation is also observed. However, the main biological function of these natural pyrazinones is yet to be discovered. The staphylococcal bioreporter assays were used to eludicdate the structure-activity relationship of a series of truncated AIP-based antagonists against the AgrC1 receptor. Promising inhibitors are then evaluated against AgrC2, AgrC3 and AgrC4. Several compounds were found to be potent low nanomolar inhibitors across all four agr groups. A bioreporter assay based on the mutant receptor A101T T104V AgrC1 in which (Ala5)AIP1 is an agonist was also used to evaluate the panel of compounds. This revealed that most of these truncated AIP-based compounds are agonists of the mutant receptor, similar to (Ala5)AIP1. However, (Ala2, Leu4, Tfh5)trAIP1 (3.23) effectively inhibited activation of this bioreporter by AIP1. Compound 3.23 was also a sub-nanomolar inhibitor of AgrC1 and a low nanomolar inhibitor in other agr groups. Compound 3.23 is the most potent AgrC1 inhibitor discovered to date and, furthermore, its effects are likely to be less susceptible to mutations within the AgrC receptor. The depsipeptide natural products, solonamides, were synthesised using two uniquely different strategies. Development of a new synthetic strategy produced analogues with a high yield and diastereomeric excess in contrast with previous low yielding or non-stereoselective strategies. Their previously reported inhibition of the agr system was confirmed and fully quantified. Solonamide A and B inhibit activity in all four agr groups. Expression of toxic shock syndrome toxin-1 (TSST-1) and α-hemolysin were reduced in Staphylococcus aureus KH1187A. Schild analysis of data from agr bioreporters revealed that the inhibition is not competitive (as previously reported), but the solonamides act as negative allosteric modulators of both the AgrC1 and AgrC2 receptors, interacting with a new putative conserved allosteric binding site. Weak agonism at high concentrations was also discovered, which has not been previously observed. A panel of analogues was produced to assess the SAR with AgrC1. Modifications of the solonamide scaffold achieved mild improvements of physical characteristics and potency.